2018
DOI: 10.24297/jssr.v12i1.7298
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and Self-Compassion Based Interventions for Substance Use Disorders: A Literature Review

Abstract: This literature review examines eight peer reviewed studies reporting on the efficacy of mindfulness-based and self-compassion-based interventions for adults diagnosed with substance use disorders. Prevalence of substance use disorders is provided, and relevant definitions are discussed. The syndrome model of addiction is advanced as an etiological explanation, and the search methodology described. Results of this literature review support mindfulness training as an effective intervention for substance use dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…One investigation demonstrated the way in which patients at a residential SUD facility increased self-compassion while reducing guilt and shame after a 4-week self-compassion intervention (Held et al, 2018). Phelps et al (2018) found that lower self-compassion was associated with a higher risk of SUD, while Platt et al (2018) indicated that self-compassion interventions produced speedier reductions of daily cigarette smoking.…”
Section: Act and Self-compassionmentioning
confidence: 99%
“…One investigation demonstrated the way in which patients at a residential SUD facility increased self-compassion while reducing guilt and shame after a 4-week self-compassion intervention (Held et al, 2018). Phelps et al (2018) found that lower self-compassion was associated with a higher risk of SUD, while Platt et al (2018) indicated that self-compassion interventions produced speedier reductions of daily cigarette smoking.…”
Section: Act and Self-compassionmentioning
confidence: 99%